2014
DOI: 10.1590/s0100-06832014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of field slope and coffee plantation age on the physical properties of a red-yellow Latosol

Abstract: SUMMARYIn modern agriculture, several factors cause changes in the soil physical properties. The time of establishment of a crop (plantation age) and the slope are examples of factors that moderate the impact of mechanized operations on the soil structure. The objective of this study was to analyze the effect of machinery traffic on the physical properties of a Red-Yellow Latosol under coffee plantations with different ages (2, 7, 18, and 33 years) and slope positions (3, 9 and 15 %). Samples were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This result is in agreement with that of Araujo-Junior et al (2011), who studied areas cultivated with Arabica coffee under different weed management schemes. Also for Arabica coffee, Iori et al (2014) observed higher soil density and soil RP and a decrease in total pore volume at the traffic row, which became more pronounced over time.The lowest TP and macroporosity were observed for the soil under conventional management (Fig. 4), for which at least three tractor runs per year were performed.…”
Section: Soil Porositymentioning
confidence: 82%
See 1 more Smart Citation
“…This result is in agreement with that of Araujo-Junior et al (2011), who studied areas cultivated with Arabica coffee under different weed management schemes. Also for Arabica coffee, Iori et al (2014) observed higher soil density and soil RP and a decrease in total pore volume at the traffic row, which became more pronounced over time.The lowest TP and macroporosity were observed for the soil under conventional management (Fig. 4), for which at least three tractor runs per year were performed.…”
Section: Soil Porositymentioning
confidence: 82%
“…However, it has its limitations, as for example the cost of certification, lack of specialized professionals and specific research, besides difficulties in replacing chemical fertilisation and achieving better prices. Because soil's physical properties are influenced by the management system adopted, information of the soil properties are important for optimisation and success of any agricultural activity (Araujo-Junior et al, 2011;Cortez et al, 2014;Iori et al, 2014;Sousa Neto et al, 2014). Changes in soil physical properties may influence pore volume and geometry, mechanical resistance, and the storage and movement of water, gases and heat of the soil and may therefore affect root and plant development (Secco et al, 2009;Oliveira et al, 2012;Fagundes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%